Development and introduction of distance learning courses on tactical disciplines in higher military education institutions - Radchenko, K. A.; Zmiievskyi, G. A.; Petruk, O. V. (Problems of Engineer-Pedagogical Education, 2018)
In article on the basis of a comprehensive analysis and generalization of experience of the use of distance learning information technologies in higher educational institutions of Ukraine, suggestions for their use in the system of national military education are formed. It is determined that one of the main directions of the use of information technologies to improve distance learning is the development and implementation of personalized learning systems. It is proved that one of the best and the most widespread personalized learning systems is the Moodle platform. The paper offers suggestions for its adaptation to the educational process of higher military educational institutions and makes recommendations for the design, development and implementation of distance training courses on tactical disciplines in the system of national military education. Special attention is drawn to the development of materials that are placed and circulate in the system and the organization of the distance learning unit of tactical disciplines. The article highlights a number of specific requirements that should necessarily be taken into consideration by higher education teachers who develop personal educational systems. The suggested approaches to creating distance learning courses and using personalized learning systems should finally lead to the empowerment of professional and educational activities, prove to be cost-efficient and focus on personal learning goals of the military education student in accordance with professional competencies.